Synthesis and anticonvulsant activity evaluation of n-[(2,4-dichlorophenyl)methyl]-2-(2,4-dioxo-1h-quinazolin-3-yl)acetamide novel 1-benzylsubstituted derivatives - El Kayal, Wassim; Severina, Hanna; Tsyvunin, Vadim; Zalevskyi, Sergiy; Shtrygol’, Sergiy; Vlasov, Sergiy; Golovchenko, Olga; Kovalenko, Sergiy; Georgiyants, Victoriya (ScienceRise: Pharmaceutical Science, 2022)
The aim. Synthesis of 1-benzylsubstituted derivatives of N-[(2,4-dichlorophenyl)methyl]-2-(2,4-dioxo-1h-quinazolin-3-yl)acetamide, and determination of affinity to GABAergic biotargets with the following anticonvulsant activity estimation using PTZ-induced seizures model in mice. Materials and methods. Standard organic synthesis methods were used; the structure of the synthesized compounds was proved by elemental analysis, 1H and 13C NMR spectroscopy, and LC/MS method; composition of the synthesized compounds – by elemental analysis, their individuality – by TLC and LC/MS methods. AutoDockTools-1.5.6, as well as AutoDock Vina software, was used to perform molecular docking. Anticonvulsant activity was studied using pentylenetetrazole-induced seizures in mice. Results. A targeted N-[(2,4-dichlorophenyl)methyl]-2-(1-(R-benzyl)-2,4-dioxo-quinazolin-3-yl)acetamides were obtained by alkylation of N-[(2,4-dichlorophenyl)methyl]-2-(2,4-dioxo-1H-quinazolin-3-yl)acetamide by corresponding 1-chloromethylbenzene in dimethylformamide environment with excess of potassium carbonate at a temperature 70-80 ˚С. Prediction of activity of 1-benzyl derivatives in the pentylenetetrazole-induced seizures in an in vivo experiment was carried out according to the obtained results of docking studies – affinity calculation for GABA receptor and GABA enzyme active sites, as well as analysis of conformational placement in them. In relation to the binding energy, the studied ligands were inferior to the reference drugs: GABA receptor positive allosteric modulators – benzamidine and diazepam, and GABA inhibitor – vigabatrin. The synthesized substances did not show anticonvulsant activity: only 2 compounds have shown a tendency to their activity manifestation according to the criterion of integral protective indicator – reduction of mortality by 17 % compared to control, as well as prolonging the time death of the animals. Comparison with the preliminary obtained results of the activity of the promising anticonvulsant N-[(2,4-dichlorophenyl)methyl] -2-(2,4-dioxo-1H-quinazolin-3-yl) acetamide N-[(2,4-dichlorophenyl)methyl]-2-(2,4-dioxo-1H-quinazolin-3-yl)acetamide made possible to prove the pharmacophore role of the cyclic amide fragment in anticonvulsant activity manifestation. Conclusion. The synthesis of N-[(2,4-dichlorophenyl)methyl]-2-(1-(R-benzyl)-2,4-dioxo-quinazolin-3-yl)acetamides, which have not still described in the literature, was carried out, as well as the structure of the mentioned compounds was proved. Unfortunately, the substances did not show anticonvulsant activity on the model of pentylenetetrazole-induced seizures. However, the obtained results allowed establishing the key role of the NHCO cyclic fragment on anticonvulsant activity. A positive correlation between the results of in vivo studies and in silico calculations was found – the model of pentylenetetrazole-induced seizures and docking into the active sites of PAMs GABAА receptor and enzyme inhibitor GABAАТ, which allows to recommend the given docking methodology as a tool to streamline and optimize the screening on the mentioned model